MEKANISME PEMBERHENTIAN HAKIM MAHKAMAH KONSTITUSI SEBELUM HABIS MASA JABATANNYA - Purnamawati, Evi (Faculty of Law, University of Palembang, 2024)
This research uas used normative jusdical about Constitutional Court Judges to be respectfully dismissed according to Law No. 7 of 2020 concerning the Constitutional Court and what is the legal meaning of Constitutional Court Decisions which are Final and Binding. The results of research on the dismissal of constitutional judges in Law 24/2003 as amended into Law Number 7 of 2020 concerning the Constitutional Court Become a Law and in more detail regulated in Constitutional Court Regulation Number 4 of 2012 concerning rocedures for Dismissing Constitutional Judges (